Intent to transfer learning amongst adult learners with differential learning orientations (Journal of Applied Learning and Teaching, 2023)
In Singapore, the government has invested significant resources into its SkillsFuture training programmes, which were established with the goal of ensuring that the skills of workforce members remain current and continue to meet the demands of the global economy. To ensure that these initiatives yield the best outcomes, however, learners must actually transfer what they have learned to their workplaces post-completion. The present study drew upon data collected as part of a larger research programme that focused on the topic of adult learners’ motivations and intent to transfer in further learning programmes. In the present study, cluster analysis was used to identify whether adult learners in one polytechnic (n=444) fell into distinct ‘learning orientation’ profiles based on their learning motivation goals and levels of intrinsic and extrinsic motivation to learn. This analysis suggested three distinct learning orientation profile clusters (Idealists, Self-Actualists and Pragmatists), who differed significantly in terms of their learning motivation and intent to transfer. Other differences observed between these clusters (i.e., whether they received rewards for programme completion; whether they were given a choice about enrolling into the training programmes; in the level of support they received to attend the programmes; and the perceived relevance of the programmes to their own situations) also underscored potential ways in which the SkillsFuture initiative and associated further learning programmes could be enhanced to maximise their ultimate benefits for workplaces. Implications for policies and strategies to achieve this goal are discussed.